Fuzzy cognitive mapping and photovoice: A pilot of a novel participatory methodology for addressing equity in community resilience research. Issue 1 (2nd January 2023) - Cafer, Anne M.; Gordon, Kymberle; Mann, Georgianna; Kaiser, Kimberly
ABSTRACT: This manuscript introduces a novel participatory mixed methods approach that combines fuzzy cognitive mapping (FCM) and photovoice. This pilot is designed to explore the possibilities for this mixed methodology to address two key gaps in the community resilience literature: (1) narrow focus on disaster-based or acute resilience and (2) lack of historically marginalized voices. This work was conducted in a rural, Black, Southern community. This pilot study suggests that while the proposed method does allow for the prioritization of marginalized voices and for a systems level approach to non-disaster resilience building; the FCM/photovoice combination presents limitations in interpretation for non-discrete decision-making. This method can be overwhelming for participants. Further research is needed to refine the protocol for its use in multiple decision-making processes within larger local phenomenon. Additionally, the combination of narrative storytelling and empirical analysis presents a unique opportunity for informing policy. This work is part of a larger project focused on the linkages between food environment, health, and general community resilience (Mann et al., 2020). It is important to emphasize that the purpose of this article is merely to present this method as an avenue for studying community resilience. A more robust analysis of the data collected as part of this study has been published elsewhere in more detail (Mann et al., 2020).